PERILAKU PENCARIAN INFORMASI DI KALANGAN PARA PENGRAJIN GOLOK (Studi Kasus Perilaku Pencarian Informasi Para Pengrajin Golok di Kampung Galonggong Tasikmalaya) - Gumilar, Rizky Agung; Winoto, Yunus; Anwar, Rully Khairul (Jurnal Kajian Informasi dan Perpustakaan, 2016)
The purpose of this study is to disscussed about how the information behavior of the machetes craftsmen in the village Galonggong Tasikmalaya to search information to meet the needs of the information. The research methodology used in this study is a qualitative method with case study approach. The data collection was done by in-depth interviews, observation, and literature. The informant are four craftsmen who life and work in kampong Galonggong Tasikmalaya, selected through a purposive sampling of which is taking a data source with a certain considerations. The data collection was done by in-depth interviews, observation, and literature. The informant are four craftsmen who life and work in kampong Galongong Tasikmalaya. consideration this particular is a craftsman who has more than 10 years, and has been active in the search for information using many sources, both by using media-based communications and information technology as well as using conventional media such as books or small notes or also conduct discussion with colleagues to meet their information needs. The result showed that all the informants go through several stages of information search, there are five major stages that artisans do, namely the prefix stage, the stage of selection of topics, focusing the selection stage, the information gathering stage and the last stage is the presentation of information.Penelitian ini bertujuan untuk membahas tentang bagaimana perilaku para pengrajin golok di kampung Galonggong Tasikmalaya dalam melakukan pencarian informasi untuk memenuhi kebutuhan informasinya. Metodologi penelitian yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan studi kasus. Pengumpulan data dilakukan dengan wawancara mendalam, observasi, dan studi pustaka. Informan merupakan 4 orang pengrajin yang berada dikampung Galonggong Tasikmalaya, yang dipilih melalui cara purposive sampling yaitu pengambilan sumber data dengan pertimbangan tertentu. Pertimbangan tertentu ini adalah pengrajin yang memiliki pengalaman lebih dari 10 tahun, serta aktif dalam mencari informasi menggunakan berbagai sumber baik itu dengan menggunakan media berbasis teknologi komunikasi dan informasi maupun menggunakan media konvensional seperti buku atau catatan kecil atau juga melakukan forum diskusi bersama rekan seprofesi untuk memenuhi kebutuhan informasinya. Hasil penelitian ini menunjukan bahwa semua informan menempuh beberapa tahapan pencarian informasi, ada 5 tahapan besar yang pengrajin lakukan, yakni tahap awalan, tahap pemilihan topik, tahap pemilihan fokus, tahap pengumpulan informasi dan yang terakhir tahap penyajian informasi.